Piloting teletherapy for children with hearing loss in Malaysia - Fathi Othman, Basyariatul; Abdul Aziz, Nurul Akmar (Jurnal Pendidikan Bitara UPSI, 2019)
Teletherapy is defined as utilising telecommunications technology for professionals to deliver their therapy sessions to the client from a distance. Hear Me, a national parent support group for children with hearing loss, initiated a small-scale teletherapy programme. This pilot teletherapy programme addresses the availability of, and accessibility to, quality therapy services provided by trained professionals. Teletherapy was provided to four families with a child with significant sensorineural hearing loss prelingually. All children use spoken language as their mode of communication. Each child received two speech-language therapy sessions and one literacy intervention session, per month, for six months. Each session consisted of (i) direct instructions to the child, and (ii) parent coaching to enable them to become skilled facilitators to their child. Two professionals were involved - one is a speech-language pathologist specialised in spoken language intervention for children with hearing loss, and the other is a teacher-of-the-deaf who is also trained in literacy development. Both professionals have graduate level education and training in the area of paediatric hearing loss. The platform used for teletherapy was Zoom®, chosen for its secured feature that protects sensitive and confidential information. The families accessed the virtual therapy room either via a specific web address on their browser, or by installing Zoom® application on their device. An exit survey shows that in general, both parents and professionals reported positive outcomes for teletherapy not only for the children, but also for the parents in supporting their child in the home environment. The ease and practicalities of teletherapy as a mode of service delivery, along with its contributions and limitations will be discussed. The findings from this pilot teletherapy programme suggest its potential to be delivered in a wider scale to other children in need of quality therapy services.